170 Perceptions of Relevance and Delivery Modes of Research Best Practices Training for Community Health Workers and Promotoras. (April 2022) - Varma, Deepthi Satheesa; Samuels, Elias; Sprioff, Meghan; Price, Melisa; Loera, Gustavo; Murphy, Luisa; Sergio-Aguilar-Gaxiola,; Cottler, Linda B.; Murphy, Susan
Abstract : OBJECTIVES/GOALS: Researchers include community health workers and promotoras (CHW/Ps) on research teams to increase community engagement; however, no formal training on research best practices exists for this group. Study objectives were to examine perceived relevance of a new culturally and linguistically appropriate CHW/P training and optimal delivery modes. METHODS/STUDY POPULATION: We conducted six focus groups (FGs), three each in English and Spanish, at three study sites, University of Florida, University of Michigan, and University of California Davis from February to August 2021. The CHWs/Ps were purposively selected to include diverse age, race/ethnicity, educational level, and work experience. Separate FGs were conducted for CHWs/Ps in English and Spanish as appropriate. All FGs were audio recorded, translated to English from Spanish, transcribed and analyzed using RADaR (Rigorous and Accelerated Data Reduction) technique. RESULTS/ANTICIPATED RESULTS: Forty CHWs/Ps (95% women, mean age 45) participated, with the majority (58%) identifying as Hispanic/Latino. Of the sample, most identified as White (50%) or Black (25%). The proposed training was mentioned as relevant and would help them to be confident, comfortable, knowledgeable and effective in the community. Online training, though advantageous due to its flexibility also reportedly had barriers such as internet access, computer availability and technological know-how of CHWs/Ps. A hybrid training approach, online plus peer-led, was recommended due to the importance of personal guidance by an experienced CHW/P' especially for a newly recruited CHW/P. DISCUSSION/SIGNIFICANCE: Findings indicated that a culturally and linguistically appropriate CHW/P training that is flexible and easily accessible in its mode of delivery is relevant and useful. In-person guidance to a new CHW/P was reported as an important training component. Poster will include the detailed quotes on relevance, usefulness, and mode of delivery of training.